Hubungan Usia, Massa Lemak, dan Indeks Massa Tubuh dengan Nyeri Punggung Bawah pada Karyawan Rumah Sakit Umum Universitas Muhammadiyah Malang - Anung Putri Illahika; Annisa Hanifwati; Risma Karlina Prabawati; Muh. Rizal Hidayat; Amatullah Rusydah Aqiilah; Deny Dwi Julianti; Nielanawalul Putri Rosyanti (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Low back pain (LBP) is a leading cause of global disability, significantly impacting work productivity. Known risk factors include age and obesity. However, while Body Mass Index (BMI) is a common indicator of obesity, BMI provides limited insight into true body composition. This study used Bioelectrical Impedance Analysis (BIA) to provide a more precise measurement of fat mass and to analyze its correlation with LBP, along with age and BMI, among employees at the University of Muhammadiyah Malang (UMM) General Hospital. The study used a cross-sectional design involving 112 hospital employees. Age was collected through a questionnaire. Fat mass was measured using the Tanita BC-418, and LBP was assessed using the Nordic Body Map (NBM) questionnaire, which distinguishes between complaints and disabilities. Statistical analysis used the Kruskal-Wallis test for correlations involving LBP complaints (age and fat mass) and the Spearman correlation test for correlations involving LBP disabilities (age and BMI). This study found no statistically significant correlations between the analyzed variables and LBP complaints or disabilities. Spearman's correlation test showed a weak, insignificant relationship between age and LBP disability (r=0.141; p=0.130) and between BMI and LBP disability (r=0.148; p=0.116). Similarly, the Kruskal-Wallis test did not show a significant correlation between age and LBP complaints (p=0.299) or between fat mass and LBP complaints (p=0.564). Conclusion: Age, fat mass, and BMI were not found to be significant predictors of LBP complaints or disability in this specific hospital employee population. These findings suggest that occupational or ergonomic factors may play a more dominant role in the etiology of LBP in hospital staff than anthropometric parameters alone.